The Influence of R&D Expense, Capital Structure, Quick Ratio, and Corporate Action on Stock Market Prices before and During the Covid-19 Pandemic - Shabrina Rahutami Nur Amalia (Budapest International Research and Critics University, 2022)
This article aims to reveal the effect of liquidity, profitability, macroeconomic indicators, capital structure, dividend policy, and cor-porate action on stock prices after the deadline for submitting annual financial reports to the Indonesia Stock Exchange. The study used a sample of companies listed on the Indonesia Stock Exchange in 2018-2019 from the energy, industrial, primary consumer goods, non-primary consumer goods, health, technology, and transportation and logistics sectors listed on the Indonesia Stock Exchange. The data testing technique uses random effect regression for panel data. The results showed that profitability had a posi-tive effect on stock prices. This is because the Indonesian capital market model still adheres to the earnings model compared to the dividend model in valuing shares.